Analysis of Factors Affecting Taxpayer Compliance with Land and Building Tax for Rural and Urban Tax and How it is Effecting on Receivables Land and Building Tax for Rural and Urban in Karo District - Maria Kesumawaty Sitanggang; Azhar Maksum; Murni Daulay (Institute of Computer Science (IOCS), 2021)
This study aims to analyze the factors that affect the compliance of PBB-P2 taxpayers in paying PBB-P2 and how the effect of PBB-P2 taxpayers compliance on PBB-P2 receivables. The population in this study amounted to 115,678 well-known PBB-P2 taxpayers were spread over 17 districts in Karo Regency. The sample selection method used purposive sampling technique, which samples used 249 PBB-P2 taxpayers. The type of data is primary data, which analizing working with SEM technique. This study using Lisrel as the software to resulting number. The results showed that PBB-P2 service, PBB-P2 tax sanctions, PBB-P2 knowledge, PBB-P2 taxpayers awareness, and NJOP PBB-P2 has a positive and significant effect on PBB-P2 taxpayer compliance, and PBB-P2 taxpayer compliance has a positive and significant effect on PBB-P2 receivables.